A 475-year tree-ring-width record of streamflow for the Qingshui River originating in the southern slope of the central Tianshan Mountains, China. Issue 3 (2nd July 2020) - Zhang, Tongwen; Shang, Huaming; Fan, Yuting; Yu, Shulong; Zhang, Ruibo; Qin, Li; Jiang, Shengxia
ABSTRACT: We reconstructed the streamflow of the Qingshui River, which originates from the southern slopes of the central Tianshan Mountains in western China. The correlation between the hydrometeorological data and the tree-ring chronology indicated that the influences of temperature and precipitation on the radial growth of spruces were contrary in the different periods of the growth and non-growth seasons, while the highest correlation was found between the streamflow and the chronology. Based on the results of correlation analyses, a 475-year streamflow reconstruction from the previous August to the current July for the Qingshui River was reconstructed using the regional chronology. The reconstructed streamflow series matched observations well, with 43.1% of the variation in the observed streamflow. The streamflow reconstruction had a significantly positive correlation with a gridded PDSI dataset for an area closely corresponding to the Qingshui River watershed. The 50- and 2.0–3.0-year cycles of this reconstruction were consistent with other tree-ring based hydrometeorological reconstructions, and revealed the possible influences of the Gleissberg solar activity cycle and the interannual oscillations of land–atmospheric–ocean systems. The streamflow reconstruction for the Qingshui River captures some wet/drought years noted in historical documents and two turbulent periods after 1700 in Xinjiang, and agrees well with the streamflow reconstruction for the Kaidu River. Synoptic climatology analysis revealed a relationship between anomalous atmospheric circulation and wet/dry years for the Qingshui River watershed and its surrounding area. It is likely that the path of moisture in the wet years mainly originates from the Indian Ocean.